Central Asian security : the new international context - Allison, Roy.; Jonson, Lena, 1948-; Utrikespolitiska institutet (Sweden); Royal Institute of International Affairs (London : Royal Institute of International Affairs ; Washington, D.C. : Brookings Institution Press, 2001)
"The authors in this study assess internal security policy problems and examine the security content of evolving relations between the Central Asian states and regional and international powers - specifically the stakes, interests, and policies of Russia, China, Iran, Turkey, and the United States. While new possibilities for regional security cooperation in Central Asia can be explored, there remains a danger of destabilizing rivalry, which would fracture the region and hamper economic development. These dilemmas are examined by a team of specialists from Western Europe, the United States, Russia, and China."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved
Central Asian security : internal and external dynamics / Lena Jonson and Roy Allison -- Central Asia : common legacies and conflicts / Martha Brill Olcott -- Islam in Central Asia / Alexei Malashenko -- Water in Central Asia : regional cooperation or conflict? / Stuart Horsman -- Russia and Central Asia / Lena Jonson -- The United States and Central Asia / Stephen blank -- China and Central Asia / Guangcheng Xing -- Relations to the south : Iran and Afghanistan / Edmund Herzig -- Turkey and Central Asia / Gareth M. Winrow -- Structures and frameworks for security policy cooperation in Central Asia / Roy Allison -- Conclusion : Central Asian security in the regional and international context / Roy Allison.
"In association with the Swedish Institute of International Affairs."
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: National security -- Asia, Central; Asia, Central -- Foreign relations -- 1991-; Asia, Central -- Strategic aspects; Sécurité régionale -- Asie centrale; Asie centrale -- Relations extérieures -- 1991-; Asie centrale -- Aspect stratégique.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; POLITICAL SCIENCE -- International Relations -- Diplomacy; Diplomatic relations; National security; Strategic aspects of individual places; Central Asia; Buitenlandse politiek; Veiligheidspolitiek; Internationale veiligheid; Nationale veiligheid; Internationale samenwerking; Militaire samenwerking; Midden-Azië; Since 1991; Samfundsvidenskab -- Politologi